Determinants of production and marketing of vegetables in kailali district of Nepal: Determinants of vegetable production and marketing (SAARC Journal of Agriculture, 2022)
The objective of this study was to find out the existing vegetable production and marketing practices in the Kailali district of Nepal. A total of 100 vegetable growers were selected using a simple random sampling technique. Data collection was done by using a semi-structured interview. Secondary data was collected from the reports and journal articles. Indexing techniques and descriptive statistics were used in this study. It was estimated that the average size of a household's landholding was 0.1689-0.337 hectares. Forty-eight percent of the households earned NRs 1,00,001–2,00,001/year from vegetable farming. About 93% of the farmers were interested in off-season vegetable production. Around 45% of households used different fertilizers, namely urea, DAP, and MOP. Insect and disease attacks (index value = 0.82) were the major problems. Aphid (index value = 0.818) and blight (index value = 0.768) were reported as the major pest and disease, respectively. About 47% of farmers grew hybrid seeds. Farmers sold their products in India (50%), Dadeldhura (30%), and local markets (20%).The management of insect pests and diseases, access to chemical fertilizers and hybrid seeds, and the provision of offseason vegetable production training to farmers are necessary for the promotion of commercial vegetable production in the district.SAARC J. Agric., 20(1): 239-252 (2022)